Screening the potential of Acalypha indica L. for its efficiency of removing heavy metals from contaminated soils - A.V.V.S. Swamy, V. Subhashini, (International Journal of Scientific Research and Management (IJSRM), 2017)
Heavy metal pollution causes potential ecological risk. Metals like Cadmium (Cd), Lead (Pb), Zinc (Zn) and Chromium (Cr) when present in high concentrations in soil exert potential toxic effects on overall growth and metabolism of plants and bioaccumulation of such toxic metals in the plant poses a risk to human and animal health. Many species of plants have been successful in absorbing contaminants such as lead, cadmium, chromium, arsenic, and various radionuclides from soils. In the present study Acalypha indica an herb species was used in pot experiment for phytoremediation of Pb, Ni, Zn, Cd and Cr contaminated soils. The objective of the study was to test the ability of the native plant species to absorb the heavy metals. The species grown for a period of 60 days. For every 20 days plant samples were taken from the pot and estimate total accumulation of metals in roots, stem and leaves. Bioconcentration factor (BCF) and Translocation Factor (TF) was calculated. Based on the results the species was good accumulator of lead, nickel, zinc, chromium and moderate accumulator of cadmium. The species can be recommended for the phytoextraction of lead, nickel, zinc and chromium contaminated soils.